Neuropsychiatric Features of a Cohort of Patients with Systemic Lupus Erythematosus - Moraes-Fontes, MF (2015)
In order to establish if neuropsychiatric systemic lupus erythematosus (NPSLE) can be identified by any characteristic other than those used to diagnose the neuropsychiatric (NP) disease itself, we retrospectively reviewed 98 systemic lupus erythematosus (SLE) patients followed over a mean period of 10 years. NPSLE was identified in 22 patients. Stroke and generalized seizures were the most frequent NP manifestations. The NPSLE and non-NPSLE groups were similar with regard to demographic characteristics, ACR criteria, serum autoantibodies, and frequency of hypertension and hypercholesterolemia. Of note, compared to the non-NPSLE group, NPSLE was associated with a higher frequency of smoking (78 versus 26%), organ damage (73 versus 34%), and cumulative mortality rate (14 versus 7%). The series of patients was further analysed according to the presence of antiphospholipid syndrome (APS). Significantly, the interval between the onset of NP disease and SLE diagnosis was shorter in the APS(-) (0.3 ± 1 years) than in the APS(+) (5 ± 7 years) groups. Recurrence and/or persistence of NP events were only documented in the APS(-) group. Overall cumulative mortality was highest in NPSLE and in APS(+) patients with inadequate anticoagulation control, identifying an aspect that requires improved vigilance and the development of novel therapeutic modalities.